2008
DOI: 10.1063/1.2973151
|View full text |Cite
|
Sign up to set email alerts
|

Balanced ambipolar charge carrier mobility in mixed layers for application in hybrid white organic light-emitting diodes

Abstract: We investigate the electron and hole mobility in mixed layers of N,N′-di(naphthalen-1-yl)-N,N′-diphenyl-benzidine and bis(2-methyl-8-quinolinato)-4-phenylphenolate aluminum with different mix ratios, using both space-charge limited currents of single-carrier devices with electrically doped charge transport layers and time-of-flight measurements. Both experimental methods yield consistent results. The 1:1 blend shows balanced ambipolar charge carrier transport, which is advantageous for the application as excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 14 publications
(15 reference statements)
1
61
0
Order By: Relevance
“…[10]. Agreement between the hole mobility in α-NPD extracted from device simulations and measured by TOF was reported previously by Schwartz et al [11]. In another TOF study of hole transport in α-NPD, the value σ = 0.090 eV was found from a fit to the GDM of the T dependence of the mobility [12], in excellent agreement with the value of σ = 0.087 eV.…”
Section: Introductionsupporting
confidence: 73%
“…[10]. Agreement between the hole mobility in α-NPD extracted from device simulations and measured by TOF was reported previously by Schwartz et al [11]. In another TOF study of hole transport in α-NPD, the value σ = 0.090 eV was found from a fit to the GDM of the T dependence of the mobility [12], in excellent agreement with the value of σ = 0.087 eV.…”
Section: Introductionsupporting
confidence: 73%
“…Two prior studies have measured the charge carrier mobility of the electron transport materials Tris-(8-hydroxyquinoline)aluminum (AlQ 3 ) and bis(2-methyl-8-quinolinato)-4-phenylphenolate aluminum when mixed into N,N'-di(naphthalen-1-yl)-N,N'-diphenyl-benzidine. 7,8 It was observed that increasing the fraction of the conductive material leads to a higher mobility, but no clear relation between concentration and mobility was identified. Subsequently, it was observed that the electrical properties of 4,7-diphenyl-1,10-phenanthroline (BPhen)/ tetracyanoquinodimethane (TCNQ) 9 and AlQ 3 /4,4 ′ -bis(carbazol-9-yl)-biphenyl (CBP) 10 mixed layers could be explained with an empirical scaling law:…”
mentioning
confidence: 99%
“…However, a blue fluorescent emitting layer (EML) needs to be close to the exciton recombination zone, because the diffusion length of singlet excitons is far below that of triplet excitons. 1,[11][12][13] Compared with the triplet level of yellow or green phosphorescent dopants, fluorescent materials such as p-bis (p-N,N-diphenyl-aminostyryl) benzene (DSA-ph), 4,4 0 -bis [2-{4-(N,N-diphenylamino) phenyl}vinyl]biphenyl (DPAVBi), and 2,2 0 ,7,7 0 -tetrakis(2,2-diphenylvinyl)spiro-9,9 0 -bifluorene (Spiro-DPVBi) [14][15][16][17][18] with a lower triplet level inevitably quench the triplet excitons in the exciton recombination zone, giving rise to low external quantum efficiencies (EQEs). In order to alleviate this negative effect, a kind of functional layer called interlayer has been employed in conventional hybrid WOLEDs.…”
mentioning
confidence: 99%
“…8,15,18,[23][24][25] The mixed interlayer can effectively prevent triplet quenching in a fluorescent emitter. Nevertheless, the proportions and the thicknesses of such a mixed interlayer have to be precisely controlled, which renders the device fabrication process both cumbersome and difficult to reproduce.…”
mentioning
confidence: 99%
See 1 more Smart Citation